Enhanced emotional reactivity after selective REM sleep deprivation in humans: an fMRI study - Rosales-Lagarde, Alejandra; Armony, Jorge L.; del Río-Portilla, Yolanda; Trejo-Martínez, David; Conde, Ruben; Corsi-Cabrera, Maria (Frontiers in Behavioral Neuroscience, 2012)
Converging evidence from animal and human studies suggest that rapid eye movement (REM) sleep modulates emotional processing. The aim of the present study was to explore the effects of selective REM sleep deprivation (REM-D) on emotional responses to threatening visual stimuli and their brain correlates using functional magnetic resonance imaging (fMRI). Twenty healthy subjects were randomly assigned to two groups: selective REM-D, by awakening them at each REM sleep onset, or non-rapid eye movement sleep interruptions (NREM-I) as control for potential non-specific effects of awakenings and lack of sleep. In a within-subject design, a visual emotional reactivity task was performed in the scanner before and 24 h after sleep manipulation. Behaviorally, emotional reactivity was enhanced relative to baseline (BL) in the REM deprived group only. In terms of fMRI signal, there was, as expected, an overall decrease in activity in the NREM-I group when subjects performed the task the second time, particularly in regions involved in emotional processing, such as occipital and temporal areas, as well as in the ventrolateral prefrontal cortex, involved in top-down emotion regulation. In contrast, activity in these areas remained the same level or even increased in the REM-D group, compared to their BL level. Taken together, these results suggest that lack of REM sleep in humans is associated with enhanced emotional reactivity, both at behavioral and neural levels, and thus highlight the specific role of REM sleep in regulating the neural substrates for emotional responsiveness.